Optimasi Asam Humat Gambut dan Dosis Pemupukan untuk Peningkatan Produktivitas Bawang Merah di Lahan Pasang Surut - A. Haitami; Wahyudi Wahyudi; Nariman Hadi (Universitas Gadjah Mada, 2026)
Tidal areas have significant potential for shallot cultivation, but are hampered by soil acidity and low nutrient availability. This study aimed to determine the effect of peat humic acid and NPK fertilizer on shallot growth and productivity in tidal areas. This study used a Split-Plot factorial design with two factors: The main plot is the dose of peat humic acid consisting of 4 treatment levels, namely without peat humic acid (control), 0,08 g/plant, 0,16 g/plant, and 0,32 g/plant, while the subplot is the fertilizer dose consisting of 4 treatment levels, namely without fertilization (control), 75 kg Urea ha⁻¹ + 75 kg ZA ha⁻¹ + 125 kg SP-36 ha⁻¹ + 75 kg KCl ha⁻¹, 100 kg Urea ha⁻¹ + 100 kg ZA ha⁻¹ + 175 kg SP-36 ha⁻¹ + 100 kg KCl ha⁻¹, and 125 kg Urea ha⁻¹ + 125 kg ZA ha⁻¹ + 225 kg SP-36 ha⁻¹ + 125 kg KCl ha⁻¹. The parameters observed included plant height, number of tubers, fresh tuber weight, dry tuber weight, number of tillers, and productivity. The results showed that peat humic acid and NPK fertilization each had a very significant effect on all growth parameters and yield, but no significant interaction was found between the two factors. The best results were obtained in the combination treatment of peat humic acid 3 g/plant and NPK fertilizer 75% of the recommended dose, which resulted in a plant height of 34,05 cm, 9 tubers per plant, fresh tuber weight of 71 g, dry tuber weight of 60 g, 5,10 tillers per plant, and a productivity of 10 tons/ha. Soil analysis showed a neutral pH of 7,53, a very high organic C content of 26,19 mg/L, and adequate macronutrient content. These results indicate that the application of peat humic acid 3 g/plant combined with 75% of the recommended dose of NPK fertilizer is the optimal combination for shallot cultivation in tidal land, achieving a productivity increase of 97,69% compared to the control without treatment.